PARTIAL DIFFERENTIAL EQUATIONS AND SOME OF THE APPLICATIONS - Dr. Ravi. M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper attempts to study the partial differential equations and some of the applications on it.Basic concepts are studied.Common PDEs in different branches,solution methods,boundary and initial conditions are studied. Application of PDEs in Heat Conduction in Solids (Diffusion Equation) and Application of PDEs in Thermal Management of Electronics (Heat Equation) are studied.Conclusions are given where ever necessary and future directions are given at the last.